MYD88 L265P mutation contributes to the diagnosis of Bing Neel syndrome. (27th August 2014) - Poulain, Stéphanie; Boyle, Eileen M.; Roumier, Christophe; Demarquette, Hélène; Wemeau, Mathieu; Geffroy, Sandrine; Herbaux, Charles; Bertrand, Elisabeth; Hivert, Bénédicte; Terriou, Louis; Verrier, Albert; Pollet, Jean Paul; et al.
Summary Bing‐Neel syndrome (BNS), a rare neurological syndrome associated with Waldenström macroglobulinaemia (WM), is a direct involvement of the central nervous system by lymphoplasmacytoid cells characterized with an adverse prognostic. The MYD88 L265P mutation has been identified in the vast majority of patients with WM. The diagnosis of BNS is often challenging because of the variety of clinical presentations associated with difficult histological techniques. We hypothesized that identification of MYD88 L265P mutation in the cerebrospinal fluid (CSF) would contribute to the diagnosis of BNS in addition to imaging, flow cytometry and cytology. We identified MYD88 L265P mutation in the CSF and the bone marrow of all cases of BNS using quantitative polymerase chain reaction qPCR and Sanger sequencing. Copy neutral loss of heterozygosity including MYD88 was observed in one case. No mutation of CXCR4, CD79A and CD79B was observed in parallel. We further showed that monitoring the quantitative expression of MYD88 L265P mutation might be a useful molecular tool to monitor response to chemotherapy using qPCR. In conclusion, identification of MYD88 L265P mutation might be a new molecular‐based biomarker tool to add to the diagnostic and monitoring armamentarium for BNS.